Effects of Thinning on Dynamics and Drought Resistance of Aspen-White Spruce Mixtures: Results From Two Study Sites in Saskatchewan - Comeau, Philip G. (Frontiers in Forests and Global Change, 2021)
Drought stress associated is causing increased mortality and reduced growth of trees in drier portions of the boreal forests of western Canada with both warming and drought expected to increase over the coming decades. While thinning is often shown to reduce drought stress, there is little information on its effects in stands comprised of mixtures of trembling aspen and white spruce that are common in the forests of this region. This study examined effects of precommercial thinning on aspen and spruce growth, response to drought stress, and stand dynamics for two study sites located in Saskatchewan, Canada. In unthinned plots aspen densities declined from initial densities of 40,000 to 200,000 trees ha-1 to 2,639 trees ha-1 at age 26. Twenty-one years after thinning (ie. at age 26) diameter of aspen and spruce had increased, with largest trees being found at the lowest aspen densities (200 aspen ha-1 for aspen and 0 aspen ha-1 for spruce). Aspen density affected average height but not height of aspen top height trees. Spruce height decreased significantly with increasing aspen density. Crown width and live crown ratio of both aspen and spruce declined with increasing aspen density. Data from cores collected from aspen and spruce indicate significant positive effects of tree size (basal area at beginning of the year), and CMI (Climate Moisture Index) on basal area increment of both aspen and spruce while increasing aspen basal area (m2ha-1) had negative effects on aspen and spruce growth. Increasing tree size (basal area) and aspen competition (basal area ha-1) both had negative effects on drought resistance and resilience for both aspen and spruce. Yield projections provided by the Mixedwood Growth Model (MGM) suggest that the mixture of 1500 aspen ha-1 and 1000 spruce ha-1 has the potential to provide a 23% increase in total mean annual increment (MAI) with a single harvest at age 100, compared to unthinned aspen stands, but with a 44% reduction in spruce MAI compared to pure spruce stands. Thinning of aspen to densities below 4000 trees ha-1 at age 5 resulted in reduced aspen yields but increased spruce yields.